A Study of Histopathological Spectrum of Ovarian Neoplastic and Non-Neoplastic Lesions at Teaching Hospital, Ahmedabad - Patel, Piyush Ashokbhai; Patel, Deval Narendrakumar; Patel, Mona Manubhai; Bhalodia, Jignasa Nathalal (Annals of Pathology and Laboratory Medicine, 2020)
Background: Ovarian carcinoma is one of the most common gynecologic cancers that ranks third after cervical and uterine cancer. ovarian lesions are neoplastic and non neoplastic and many neoplastic lesions are asymptomatic and possess great challenge to the gynecological oncologist. Aims & Objectives: To analyze frequency, age distribution and histopathological spectrum of ovarian lesions at teaching hospital, Ahmedabad. Materials & Method: This study was undertaken between period of 1st January 2018 to 29th February 2020 at Department of Pathology, GMERS Medical college, sola, Ahmedabad. H and E stained slides were examined by light microscopy and histopathological type of lesions were classified according to World Health Organization (WHO) classification -2014. Results: There were total 182 cases of ovarian lesions. 56(30.76%) cases are neoplastic, among them only 6(10.71%) were malignant. Surface epithelial tumor (n=27 cases, 48.21%) were most common neoplastic lesion while sex cord stromal tumor (n=8 cases,14.29%) were least common. Most common age group affected for neoplastic lesions was 31-40 years. Conclusion: We found that ovarian lesions affect wide variation of age starting from 11 years young patient to 65 years old patients. Non neoplastic lesions were almost double in prevalence than neoplastic lesions. Histopathological analysis according to WHO classification reveal that surface epithelial tumors and germ cell tumors were forms the majority of neoplastic lesions.